(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Nowadays we are increasingly concerned with humanitarian problems considering that there are, have always been and will be groups of people whose matter of life and death are, have been and will be threatened by disasters, because that is the world we live in. Reviving and reinterpreting humanitarian crises of the past, finding the causes, re-evaluating the solutions of the situation, will provide us with a new knowledge to cope more easily with similar humanitarian problems of today or tomorrow. Methodology: I find it important to broaden the range of causes of commonly known humanitarian problems, so we should include the well-known fact that political regimes and undemocratic governments that are violent and contrary to human nature induce serious humanitarian crises and even humanitarian disasters. In my study I review the humanitarian problems of the GDR citizens, looking for the causes, observing the processes, analysing the political missteps and interpreting the motives of those involved. I follow the processes by monitoring the behaviour of the leaders of the states concerned, the motives behind their decisions, and then draw conclusions. Findings: Due to the emerging humanitarian crises states, their leaders and the citizens have to face clear facts. The situation must be managed, the disaster must be prevented, the danger averted and the situation restored. Value: The conclusion of my study is that without NGOs (Non-governmental organisations) the state bodies cannot or will find it very difficult to manage and solve this, and therefore cooperation with NGOs is necessary.